2014
DOI: 10.1103/physrevlett.112.098302
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous Shear Thickening without Inertia in Dense Non-Brownian Suspensions

Abstract: A consensus is emerging that discontinuous shear thickening (DST) in dense suspensions marks a transition from a flow state where particles remain well separated by lubrication layers, to one dominated by frictional contacts. We show here that reasonable assumptions about contact proliferation predict two distinct types of DST in the absence of inertia. The first occurs at densities above the jamming point of frictional particles; here, the thickened state is completely jammed and (unless particles deform) can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

46
630
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(680 citation statements)
references
References 43 publications
46
630
2
2
Order By: Relevance
“…and this could possibly explain the discrepancy between experiments. Note that friction is also believed to play a major role in jamming and discontinuous shear-thickening (Seto et al 2013;Wyart & Cates 2014). A second potential cause for the noted scatter in normal stresses is the presence of particle roughness.…”
Section: Introductionmentioning
confidence: 99%
“…and this could possibly explain the discrepancy between experiments. Note that friction is also believed to play a major role in jamming and discontinuous shear-thickening (Seto et al 2013;Wyart & Cates 2014). A second potential cause for the noted scatter in normal stresses is the presence of particle roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of finite size effects in DST measurements [2,11], at sizes up to 100 particles, questions the idea that DST is a purely local phenomenon. In this context, it is unclear how a phase diagram for the local response can be deduced from experimental data and compared with numerical [5], and theoretical [6] works. This situation motivates us to study DST in cornstarch [15], the well-known system for this phenomenon, while accessing experimentally the local response.…”
Section: Introductionmentioning
confidence: 99%
“…In numerical simulations DST was observed in systems which are forced to remain homogeneous by periodic boundary conditions [5]. It was thus suggested that it might arise from a jump of the local response, which occurs at fixed packing fraction, and is caused by the proliferation of frictional contacts [5,6]. Examples abound, however, in granular suspension rheology where the macroscopic response is sharply different from the local behaviour: the apparent yield stress [13,14] or a transient DST behavior [10], for example, were both shown to result from the emergence of flow inhomogeneities due respectively to density differences and migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been related to the propagation of dynamic jamming fronts in the bulk [18] but the mechanism remains unclear and overlooks the role of fluid/grains couplings, which are known to strongly affect the transient behavior of saturated granular materials [2,20,21]. Whether impact-activated solidification relies on such couplings or on the complex rheology of the suspension is a pivotal question for clarifying the physics of shear-thickening fluids -a still highly debated topic [23][24][25][26][27].The objective of this Letter is to address these questions and elucidate the role of the interstitial fluid and the initial volume fraction on the diverse impact phenomenology observed in granular materials and dense suspensions during the last decade. To avoid difficulties associated with colloidal interactions between particles (like in shear-thickening suspensions) or fluid compressibility (like in powders in air), we study here the impact of a freely-falling rigid sphere on a simple granular suspension [28] made up of macroscopic, heavy particles (glass beads in the range 0.1-1 mm) immersed in an incompressible liquid (water, viscous oil).…”
mentioning
confidence: 99%